A review of Gongylonema spp. (Nematoda: Gongylonematidae) in North American rodents with description of a new species from the cotton rat, Sigmodon hispidus (Mammalia: Cricetidae) - Kinsella, John M.; Robles, Maria Del Rosario; Preisser, Whitney C. (Zootaxa, 2016)
Gongylonema archboldi n. sp. (Nematoda: Gongylonematidae) is described from tunnels in the gastric mucosa of the stomach of the cotton rat (Sigmodon hispidus) from Highlands County, Florida, U.S.A. Measurements are also given for specimens from cotton mice (Peromyscus gossypinus), oldfield mice (Peromyscus polionotus), Florida mice (Podomys floridanus), and golden mice (Ochrotomys nuttalli) from the same locality. Additional specimens were collected from the cotton rat and the rice rat (Oryzomys palustris) from Berry Island, San Patricio County, Texas. The new species is differentiated from congeners by a combination of the following characters: length of the left spicule, length and shape of the gubernaculum, distribution of cuticular bosses, length of esophagus, and distance of the vulva from the posterior end. The status of the genus Gongylonema in North American rodents is reviewed.